Postoperative outcomes of robotic-assisted lobectomy in obese patients with non-small-cell lung cancer. (22nd November 2019) - Casiraghi, Monica; Sedda, Giulia; Diotti, Cristina; Mariolo, Alessio Vincenzo; Galetta, Domenico; Tessitore, Adele; Maisonneuve, Patrick; Spaggiari, Lorenzo
Abstract: : OBJECTIVES: The aim of this study was to assess the postoperative outcomes of robotic-assisted lobectomy in obese patients to determine the impact of the robotic approach on a high-risk population who were candidates for major pulmonary resection for non-small-cell lung cancer (NSCLC). METHODS: Between January 2007 and August 2018, we retrospectively reviewed the medical records of 224 obese patients (body mass index ≥ 30) who underwent pulmonary lobectomy at our institution via robotic-assisted thoracic surgery (RATS, n = 51) or lateral muscle-sparing thoracotomy ( n = 173). RESULTS: Forty-two patients were individually matched with those who had the same pathological tumour stage and similar comorbidities and presurgical treatment. The median operative time was significantly longer in the RATS group compared to that in the thoracotomy group (200 vs 158 min; P = 0.003), whereas the length of stay was significantly better for the RATS group (5 vs 6 days; P = 0.047). Postoperative complications were significantly more frequent after open lobectomy than in the RATS group (42.9% vs 16.7%; P = 0.027). After a median follow-up of 4.4 years, the 5-year overall survival rate was 67.6% [95% confidence interval (CI) 45.7–82.2] for the RATS group, and 66.1% (95% CI 46.8–79.9) for the open surgery group (log-rank P = 0.54). The 5-year cumulative incidence of cancer-related deaths was 24.8% (95% CI 9.7–43.5) for the RATS group and 23.6% (95% CI 10.8–39.2) for the open surgery group (Gray's test, P = 0.69). CONCLUSIONS: RATS is feasible and safe for obese patients with NSCLC with advantages compared to open surgery in terms of early postoperative outcomes. In addition, the long-term survival rate was comparable to that of the open approach.